2018
DOI: 10.4335/10.4335/16.1.77-106(2018)
|View full text |Cite
|
Sign up to set email alerts
|

Financial Sustainability of Municipalities and Local Governments in Small-Sized Cities; a Case of Shabestar Municipality

Abstract: Lack of a comprehensive approach to municipalities’ revenue sources in the form of macro-economic system, changes and interventions, self-reliance and self-sufficiency policy enforcement have put financial sector of municipalities in unsustainable situation. Continuing of this situation will have undesirable consequences on cities and urban management. Access to favorable and sustainable revenue sources leads municipalities to play a more active role in urban environment and properly meet the needs of citizens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…In their analysis of the phenomenon of the FA of a local government, the researchers have identified the following characteristics thereof: availability of sufficient financial resources (Burbulytė-Tsiskarishvili et al, 2018;Psycharis et al, 2016;Scutariu, Scutariu, 2015;Jemna, Onofrei, Cigu, 2014;Beer-Toth, 2009); proper allocation of the financial resources among the central and local governments (Slavinskaitė, 2017;Ulbrich, 2013;Stegarescu, 2005); capabilities and capacities for autonomous management of the financial resources by the local government (Skauronė, Miceikienė, Krikštolaitis, 2020; Tan, 2020; Kozera, Glowicka-Woloszyn, 2016; Scutariu, A., L, Scutariu, P., 2015; Cigu, 2014); sustainable assurance of balance between the revenue and expenditure (Tan, 2020;Beer-Toth, 2009;Mclure, Martinez-Vazquez, 2000); autonomous management of the tax base and tax rates (Stegarescu, 2005; Beer-Toth, 2009; Kozera, Glowicka-Woloszyn, 2016; etc. ), financial responsibility (Chen, 2022;Slavinskaitė, 2017;Oates, 1999), and financial sustainability Hajilou et al, 2018).…”
Section: Financial Autonomy Of a Local Government And Theoretical Ass...mentioning
confidence: 99%
“…In their analysis of the phenomenon of the FA of a local government, the researchers have identified the following characteristics thereof: availability of sufficient financial resources (Burbulytė-Tsiskarishvili et al, 2018;Psycharis et al, 2016;Scutariu, Scutariu, 2015;Jemna, Onofrei, Cigu, 2014;Beer-Toth, 2009); proper allocation of the financial resources among the central and local governments (Slavinskaitė, 2017;Ulbrich, 2013;Stegarescu, 2005); capabilities and capacities for autonomous management of the financial resources by the local government (Skauronė, Miceikienė, Krikštolaitis, 2020; Tan, 2020; Kozera, Glowicka-Woloszyn, 2016; Scutariu, A., L, Scutariu, P., 2015; Cigu, 2014); sustainable assurance of balance between the revenue and expenditure (Tan, 2020;Beer-Toth, 2009;Mclure, Martinez-Vazquez, 2000); autonomous management of the tax base and tax rates (Stegarescu, 2005; Beer-Toth, 2009; Kozera, Glowicka-Woloszyn, 2016; etc. ), financial responsibility (Chen, 2022;Slavinskaitė, 2017;Oates, 1999), and financial sustainability Hajilou et al, 2018).…”
Section: Financial Autonomy Of a Local Government And Theoretical Ass...mentioning
confidence: 99%
“…Financial autonomy and the issue of revenue generation are one of the key issues related to local governments worldwide. According to Hajilou et al (2018), municipalities become unsustainable due to the absence of a comprehensive approach towards implementation of the autonomy policy, sources of revenue of the financial sector, municipalities, and macroeconomic system in the area of changes and interventions. Hence, along with FA, financial sustainability is The economic theories related to growth and development enable the researchers studying the FA phenomenon to identify the endogenous factors that are important for improvement of the FA of LGUs.…”
Section: Relation Between the Phenomenon Of Financial Autonomy Of Lgus And Economic Theories And Complexity Of The Assessmentmentioning
confidence: 99%
“…This raises the issue of "convenient dependence" of municipalities on the centralized allocation in the long run. The researchers (Satoła et al 2019;Hajilou et al 2018;Jakovljevic et al 2019;Jakovljevic 2013) have therefore made attempts to validate the need for a sustainable LGUs funding system. The rationale behind this kind of system is that the financial resources received by LGUs correspond to the expenditure incurred by them in implementation of their tasks.…”
Section: Relation Between the Phenomenon Of Financial Autonomy Of Lgus And Economic Theories And Complexity Of The Assessmentmentioning
confidence: 99%
“…This green banking initiative is mutually beneficial for banks, industry and the economy. Hajilou (2018) revealed that "sustainability is meeting the needs of the present generation without compromising the ability of future generations to meet their own needs" (p. 83). Bakar (2017) stated that "the majority of companies to invest in the recycling and reuse of materials, the environmental friendly technology, internal training on green economy, the rest of the electorate and the purchase and use of materials with less impact simply because they believe that investment to ensure the preservation of nature around" (p. 139).…”
Section: Theoretical Framework Sustainable Financementioning
confidence: 99%